Comparison of Completed Cohort Fertility Rate and Total Fertility Rate in selected European countries - Kharashvili, Sopio (2024)
Nowadays, the world is struggling with challenges related to population dynamics, where fertility plays a critical role in shaping these processes. One of the most crucial concerns is the risk of the world’s population decreasing due to low fertility rates. This issue is particularly notable in many developed regions, including the European Union, where fertility rates have been declining steadily over the past few decades. As fertility rates drop below the replacement level of 2.1 children per woman, countries face significant demographic challenges that could impact economic stability, social structures, and the overall sustainability of their populations. Demographic transitions, which refer to the shift from high birth and death rates to low birth and death rates, are integral to understanding these changes. Typically, this transition involves an initial population surge followed by a stabilization or decline. In the context of many developed countries, this transition has reached a stage where low fertility rates are prevalent, leading to aging populations and shrinking workforces. These demographic shifts are significant as they influence economic growth, social services, and policy decisions. Addressing the implications of demographic transitions requires a thorough understanding of fertility indicators such as Total Fertility Rate (TFR) and Cohort Completed Fertility Rate (CCFR). Both indicators are essential for policymakers to assess and project fertility trends, understand reproductive behaviour, and anticipate future population changes. Several factors contribute to declining fertility rates, each varying in impact across different populations and cultural contexts, such as economic conditions, cultural norms, gender equality, improved reproductive health services, and the availability of contraceptive options, each of which empowers individuals to make informed decisions about their reproductive lives.